Comprehensive genome-wide identification and expression analysis of the EPF/EPFL gene family in oat - Qingxue Jiang; Lin Ma; Siyuan Guo; Xinyue Zhou; Zhipeng Zhang; Yanhong Cui; Jun Tang; Dengxia Yi; Xuemin Wang (BMC Genomics)
Abstract Epidermal pattern factor-like (EPF/EPFL) genes are a unique class of small, secreted peptides found in plants that play crucial roles in plant stress responses. A genome-wide analysis revealed 33 AsEPF/EPFL genes in oats (Avena sativa), with 28 containing the conserved EPF domain and 5 harbouring the stomagen domain. These proteins share 2–6 conserved motifs, reflecting functional modularity. The phylogenetic classification grouped these genes into five evolutionarily conserved clades containing both monocot and dicot homologues, indicating early divergence prior to monocot–dicot speciation. Expression profiling revealed distinct tissue-specific patterns: preferential expression in roots (12 genes), stems (6 genes), leaves (5 genes), and spikes (7 genes), with 3 genes showing dual peak expression in stems and leaves. Further analysis of gene expression under salt and drought stress revealed that AsEPF/EPFLs are induced by both types of stress, with different genes showing varying expression patterns under drought and salt stress. This study identified valuable candidate genes for high-yielding and stress-resistant oat breeding.